Kick and rush or valuing strategic factors in the recovery of success and financial wealth of professional football clubs - Marco Arraya (Revista Intercontinental de Gestão Desportiva, 2021)
This investigation analyzes four strategic factors – leadership, human capital, value creation, and distinctive capabilities system – influencing professional football clubs' sporting success and financial wealth. We developed two models during the investigation. The first model focuses on the four factors per se of sporting success and financial wealth, and the second model focuses on the multidimensional construct “INPUTS”. This latent factor aggregates the four distinct ones relating to the factors as a single concept. The results show that (i) only the leadership and the system of distinctive capabilities per se influence the “OUTPUTS”; and (ii) “INPUTS” have a strong influence on “OUTPUTS”, more significant than the sum of the four factors. The differential of this investigation is the conclusions related to the “INPUTS”, since the four factors are closely interconnected and, when treated as a single concept, a door is opened to capture transitory competitive opportunities and advantages through an innovation behavior. Customer and human capital centric. Furthermore, we also confirm that the distinctive capabilities system is the transmission shaft between innovation behavior and “OUTPUTS”. We did a cross-sectional survey to collect the perceptions of Portuguese football coaches. In addition, a quantitative study was used in the treatment of data, including PLS-SEM.